Analisa Sistem e-learning Pada Universitas PGRI Palembang Dengan Metode System Usability Scale (SUS) - Ayu Antika; Evi Yulianingsih (LPPM STIKI MALANG, 2023)
E-learning is an online learning system that is electronic in nature using network and computer technology, thus making it easier for students to do distance learning. Many e-learning users, one of which is the PGRI palembang university, in e-learning students can see material from lecturers in the form of media, documents, or even a video, and vice versa lecturers can also provide materials and assignments to students. However, the process often has several obstacles where users, both students and lecturers, of course feel that they have their own difficulties when operating this e-learning. The purpose of this study is to measure the level of usability where usability has 5 variables, namely: (learning ability, efficiency, memory, error, satisfaction). The instrument used in this study is the System usability scale (SUS) method, which in this method has 10 statements that represent 5 variables from usability testing. The final result of this study obtained a final score of 70.29 which means that e-learning is said to be acceptable with grade c, so that e-learning at PGRI Palembang University can be said to be effective in its use.